2010
DOI: 10.1007/s00127-010-0193-3
|View full text |Cite
|
Sign up to set email alerts
|

The recognition of mental health disorders and its association with psychiatric scepticism, knowledge of psychiatry, and the Big Five personality factors: an investigation using the overclaiming technique

Abstract: The present study examined the general public's ability to recognise mental health disorders and this ability's association with psychiatric scepticism, knowledge of psychiatry, and the Big Five personality factors. A total of 477 members of the British general public completed an overclaiming scale, in which they were asked to rate the degree to which they believed 20 mental health disorders (of which five were foils designed to resemble real disorders) were real or fake. Participants also completed a novel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 47 publications
6
39
0
Order By: Relevance
“…The results demonstrated strong support for a monological conspiracy belief system: belief in one conspiracy theory leads to belief in another conspiracy theory (Swami et al ., ; Wood et al ., ). The regression analyses showed that demographic factors, personality factors and attitude factors significantly contributed to the variance in belief in political conspiracy theories.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The results demonstrated strong support for a monological conspiracy belief system: belief in one conspiracy theory leads to belief in another conspiracy theory (Swami et al ., ; Wood et al ., ). The regression analyses showed that demographic factors, personality factors and attitude factors significantly contributed to the variance in belief in political conspiracy theories.…”
Section: Discussionsupporting
confidence: 94%
“…Self‐esteem was negatively correlated with belief in both political and medical conspiracies, supporting hypothesis 1B, however it was not a significant predictor of belief in either conspiracy type. This is in keeping with previous findings (Goertzel, ; Swami et al ., ).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Pettigrew & Tropp, ; Angermeyer et al ), personality (e.g. Swami et al ) and stereotypes (e.g. Corrigan & Watson, ).…”
Section: Discussionmentioning
confidence: 99%